Political Interference and Effectiveness of the Economic and Financial Crimes Commission, 2010-2020 - Ugochukwu Mmaduabuchi Onwunyi; Harrison Eko Akama (ESUT JOURNAL OF SOCIAL SCIENCES, 2024)
The establishment of the Economic and Financial Crimes Commission in 2002 was generally seen as a major step to eradicating corruption and other related illicit practices in Nigeria’s political space. The EFCC act of 2004 enhanced its existence and served as a legal framework that ensured full operation of the agency in Nigeria. Since its establishment, the EFCC has struggled to battle financial crimes and to a considerable extent has recorded some remarkable achievements in Nigeria. In spite of this effort, corruption has become very monstrous and obviously permeated into the very fabrics of Nigeria’s socio-economic and political life. The aim of this study is to determine the extent the Economic and Financial Crimes Commission has reduced if not completely eradicated political corruption in Nigeria between 2010 and 2020. The study also examined the operations of the EFCC, political interference on the EFCC operation and whether its activities have reduced the mismanagement of public funds by public office holders in Nigeria between 2010 and 2020. The study relied on documentary method of data collection and used content analysis and logical deductions to arrive at the conclusion of the study. We adopted structural functional theory as our theoretical framework of analysis. It argued that against the assumptions that the EFCC can stamp out political corruption in Nigeria, political corruption has assumed a worrisome dimension and has even permeated the EFCC, which is saddled with the mandate of eradicating political corruption. The study concluded that the inability of EFCC to end the increasing manifestation of political corruption over a decade of its operation can be inextricably linked to the nature and character of the Nigerian State, and more so with the question of leadership. The study, therefore, recommended radical reforms that would make EFCC more effective in tackling the menace of political corruption in Nigeria.